Environmental Policy of Uzbekistan and Measures to Reduce CO₂ Emissions (KIUT Publication, 2025)
“As a participant in the Paris Agreement, the Republic of Uzbekistan aims to reduce CO₂ emissions per unit of GDP by 35% by 2030 compared to 2010 levels. To achieve this goal, a set of measures is being implemented: increasing the share of renewable energy in electricity generation to 54% by 2030, doubling the energy efficiency of the economy, and a large-scale reforestation campaign (planting 1 billion trees over 5 years). The author analyzes the effectiveness of these initiatives, provides quantitative estimates of emission reductions, and develops recommendations to improve the efficiency of environmental policy.